(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The suspension arms in the process of fogging are made by deferent material and in that processes get various problems are found. In that paper list out that problem and solving flash wastage problem. And such problems are controlling analyses of suspension arm manufacturing process parameters. Different step by step such rolling process, blocking process and finishing process commonly affected by the process defects like folds or laps, cracks problem are found. Flash wastage is the problem controlling noteworthy constraint.